The GMS Ha Noi action plan 2018 to 2022. (Metro Manila, Philippines Asian Development Bank, 2018)
The GMS Ha Noi Action Plan 2018to2022 (HAP) addresses the unfinished and expanded agenda of the Greater Mekong Subregion (GMS) Economic Cooperation Program for the remaining 5 years of the GMS Strategic Framework 2012to2022. The HAP provides directions and operational focus to the GMS program and guides identification of projects in transport, urban development, energy, agriculture, environment, tourism, trade facilitation, human resource development, and information and communication technology. The HAPs key elements are spatial strategy focused on economic corridors; refinements in sector strategies and priorities; improvements in planning, programming, and monitoring systems and processes; and enhancements in institutional arrangements and partnerships.
Keywords: Greater Mekong Subregion -- Economic integration; Electronic books